A Legal Analysis of the Distribution of Illegal Cigarette Products and Trademark Infringement - Ikhwan Aulia Fatahillah; Santana Suryapringgana; Dimas Gibran Satrio Utomo; Aji Nugraha (Anthroposia: Journal of Social and Human Development, 2026)
Currently, the distribution of illegal cigarettes in Indonesia has evolved into a complex legal issue involving the intersection between excise tax violations and trademark infringement. This study aims to analyze the standard of “substantial similarity” in illegal cigarette branding practices, examine the forms of legal accountability imposed on perpetrators, and identify key obstacles in law enforcement. The phenomenon is driven largely by economic disparities, particularly the increase in Tobacco Product Excise (CHT), which incentivizes the emergence of organized illicit distribution networks that exploit well-known cigarette brands to mislead consumers. This research employs a normative juridical method using statutory and case approaches, focusing on legal documents and judicial precedents. The findings reveal three dominant forms of trademark infringement in illegal cigarettes, namely identical imitation, brand name modification, and packaging design replication that creates consumer confusion. Perpetrators may be held accountable through criminal sanctions under excise and trademark laws as well as civil liability based on unlawful acts under Article 1365 of the Civil Code. Although enforcement efforts such as Operation Octopus have been implemented, structural, technological, and societal constraints continue to hinder effectiveness.